2x+1-33x=6-x-5

Simple and best practice solution for 2x+1-33x=6-x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+1-33x=6-x-5 equation:



2x+1-33x=6-x-5
We move all terms to the left:
2x+1-33x-(6-x-5)=0
We add all the numbers together, and all the variables
2x-33x-(-1x+1)+1=0
We add all the numbers together, and all the variables
-31x-(-1x+1)+1=0
We get rid of parentheses
-31x+1x-1+1=0
We add all the numbers together, and all the variables
-30x=0
x=0/-30
x=0

See similar equations:

| 5(2+5n)-7n=-4-2(3-7n) | | 6n-3+n=-6+5n | | 81=4h-(-9) | | x2+6x=160 | | -4=2r–18 | | -3(3x-6)=-3x | | f-8=12+45 | | 29-3x=20 | | 7(r-6r)-r=4(r-6)-6 | | -9(k+50)=54 | | 5x0.08=0.4 | | j4+ -16= -17 | | 3x+5-5x=11 | | X+.75x=75000 | | 0=-16t^2+80t+224 | | 7u-(-20)=41 | | -9-7d=-8d+1 | | (x+3)2+(x-1)2=x+1+x+3+x+5 | | 5+8b=5(1-8b) | | 2=z-91/3 | | X+(x-15)+(x+21)=180 | | -2(x-5)=-3(x+2) | | 49x^2-64x=0. | | 60=5(12x+2) | | 3w-(-20)=74 | | 5/6t−2=3 | | 56t−2=3 | | 30+6p=4(1-5p) | | 16=31-5g | | 2x-11-4=-3 | | 4(3x-6)-4=-3x-6 | | -2+8k=-66 |

Equations solver categories